Intra-Business E-Commerce for Buku Fixi Sdn. Bhd. (Intra-CBF) - Md Saman, Nurliyana Nabilah (2025)
The Intra-Business E-Commerce System for Buku Fixi Sdn. Bhd is an ecommerce platform that has been developed to enhance the ordering process by agents within the company. The problems of the current manual process include delays in response time, human errors, and the dependency on manual payment verification. INTRA-CBF was developed with the integration of features to automate these inefficient manual processes like role-based access control, realtime inventory management, and automatic payment verification. The system was developed using an Adapted Waterfall Model combined with project methodology phases, which include planning, analysis, design, development, testing, and documentation to meet this project's objectives. From the user testing of 30 potential users, the average task time was 1.07 minutes per task, and the overall satisfaction score was 73.50 which considered as good usability score. Expert review confirmed the system was usable but offered minor suggestions for interface improvements. According to the results of the user and expert testing, INTRA-CBF has proven to be efficient, effective and user-friendly.